THURUQ TA'LIZM AL-LUGHAH AL-ARABIYAH BI MINANGKABAU MIN IM 1680-1900 M: DIRISAH TARIZKHIYAH FIZ SUMATRA AL-GHARBIYAH - Mahesa, Jaka Imam; Wargadinata, Wildana; Rosyidi, Abdul Wahab (Arabi : Journal of Arabic Studies, 2022)
Islam came to Minangkabau, bringing ritual traditions and language, which led to the spread of Arabic from Surau as a language of worship and knowledge. The study aimed to learn the Arabic learning methods in Surau in Minangkabau from 1680-1900 AD. A research method is a qualitative approach to are the type of history study: the data collection method uses interviews and documentation. As for data analysis, presentation, and inference, there is a reviewer of data using descriptive analysis and content analysis. The method of Arabic learning is Maojok Method, understanding Arabic text with Mantiq, linking Arabic studies with other sciences such as tasawwuf, The Sorogan technique, halaqah technique, the debate, and the lecture method. In the learning of Arabic learning Methods, these methods are known as special terms, namely Thariqah al-Qawa'id wa al-Tarjamah, Thariqah al-Mu'addalah, Thariqah al-Muhadharah, Thariqah al-Niqasy.